Exploring the dynamic earth (Thomson Brooks/Cole, 2007)
The investigations in this version of the GIS investigations for the earth sciences series are intended for use on campuses with ArcGIS 9.x laboratory or site licenses. All necessary software and data files should be set up and ready for you to use on campus or lab computers